'Every lover is a destroyer': queer abuse and experimental memoir in Melissa Febos' Abandon Me and Carmen Maria Machado's In the Dream House. Issue 3 (2nd September 2021) - Bussey-Chamberlain, Prudence
ABSTRACT: This article will focus on Machado's In the Dream House and Melissa Febos' Abandon Me to explore how nonfiction approaches the complexities of queer intimate partner abuse. Although working in non-fiction, Machado rewrites "the dream house" in over 100 different genres, with each small chapter of the book reaching for a new form to express the generally unspoken nature of the cycle of abuse she experienced. Febos chooses a collection of essays to document familial death, trauma, heritage, and an intense relationship that situates itself in an inarticulable space between passion and abusive dynamics. Both writers use genre to work toward a naming of abuse, or at least, finding ways to name, eschew, and queer what we understand by abuse and how its recognition is problematic in same-sex relationships.